2006
DOI: 10.1016/j.nurx.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological treatment options for pediatric migraine: An evidence-based appraisal

Abstract: Summary:The treatment of children and adolescents who suffer from migraine headaches must be individually tailored, flexible, and balanced with a blend of bio-behavioral measures, agents for acute treatment and, if needed, daily preventive medicines. While controlled data is limited, there is now enough evidence available to provide a rational framework to build treatment plans appropriate for the pediatric population. Essentially, the pharmacological management of pediatric migraine divides into agents for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This has been the case although triptans represented a therapeutic benefit over existing treatments and migraine is not uncommon in the paediatric population. No official recommendations on triptan use in children were given during the study period, but several papers reviewing the treatment options and medical trials were published [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This has been the case although triptans represented a therapeutic benefit over existing treatments and migraine is not uncommon in the paediatric population. No official recommendations on triptan use in children were given during the study period, but several papers reviewing the treatment options and medical trials were published [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Selected triptans also are approved for use in children as abortive medications. In patients with more frequent or severe headaches, prophylactic pharmacological management is considered using medications such as beta-blockers, tricyclic antidepressants, and anticonvulsants (9,42).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in this gene is particularly interesting because estrogen receptors have been implicated in disease processes in breast cancer, endometrial cancer, and osteoporosis and the ESR1 SNP rs2228480 was previously found to show association with breast cancer [140]. ESR1 is localized to chromosome 6q25.1 and is expressed in many areas of the brain regulating many functions including regulating gene expression through cell signalling affecting glutamate and serotonin synthesis and CGRP and can regulate vascular tone by stimulating release of NO [141, 142]. …”
Section: Candidate Gene Studiesmentioning
confidence: 99%